2023
DOI: 10.1039/d3ee00249g
|View full text |Cite
|
Sign up to set email alerts
|

Under pressure: offering fundamental insight into structural changes on ball milling battery materials

Laura L. Driscoll,
Elizabeth H. Driscoll,
Bo Dong
et al.

Abstract: Synthesis of Li ion battery materials via ball milling has been a huge area of growth, leading to new high capacity electrode materials, such as a number of promising disordered...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Although previous reports showed structural changes in halide SEs during MC synthesis, ,, the mechanism of ion transport and ionic conductivity, especially how MC synthesis affects the concentration and migration of Li + carriers, has not been investigated. Our findings not only expand the fundamental understanding of novel structures and their properties achieved through MC synthesis but also provide new insights on the conduction mechanism that complements the lithium-diffusion kinetics examined by computational methods . We also examined the electronic conductivity and electrochemical stability of off-stoichiometric Li–Y–Cl SEs and demonstrated the excellent cycling permeance of an NMC811 ASSB cell with a novel off-stoichiometric halide super ionic conductor, Li 2.61 Y 1.13 Cl 6 .…”
mentioning
confidence: 58%
“…Although previous reports showed structural changes in halide SEs during MC synthesis, ,, the mechanism of ion transport and ionic conductivity, especially how MC synthesis affects the concentration and migration of Li + carriers, has not been investigated. Our findings not only expand the fundamental understanding of novel structures and their properties achieved through MC synthesis but also provide new insights on the conduction mechanism that complements the lithium-diffusion kinetics examined by computational methods . We also examined the electronic conductivity and electrochemical stability of off-stoichiometric Li–Y–Cl SEs and demonstrated the excellent cycling permeance of an NMC811 ASSB cell with a novel off-stoichiometric halide super ionic conductor, Li 2.61 Y 1.13 Cl 6 .…”
mentioning
confidence: 58%
“…In particular the local pressure effects are very important, and so consequently these phases cannot be synthesised by standard solid state synthesis. 45 This is the first example of the use of recycled EV material for the synthesis of these phases. Table 3 shows the lattice parameters of the materials which are similar to literature values.…”
Section: Resultsmentioning
confidence: 96%
“…When comparing further the XRD pattern of LO2 with respect to that of LO3 (note that LO3 is obtained by ball milling LO2), the (100) and (101) diffraction peaks are no longer observable, while the (102) diffraction peak is still seen after ball milling. The reason for this phenomenon is that ball milling can selectively eliminate some crystalline planes under the action of its mechanical force, thus increasing the proportion of certain other crystalline planes. It has also been reported that ball milling can modify the phases and crystallinity of the materials and cause the broadening of diffraction peaks in some materials by displacing or creating disorder in certain lattice patterns. In the XRD patterns, the peaks seen at 15.7, 27.3, 27.9, and 48.6° are characteristic of La­(OH3) 3 (JCPDS: 06-0585). This means that some La­(OH) 3 is also present in the materials, most likely because the surfaces of La 2 O 3 can react with water vapor in the air and undergo hydroxylation to produce La­(OH) 3 .…”
Section: Resultsmentioning
confidence: 99%